Canadian Music: A Personal Perspective - Morey, Carl (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2013)
In this article the author reflects on musical life in Canada, drawing on experiential perspectives while growing up in Toronto and his career for three decades as a faculty member in musicology at the Faculty of Music at the University of Toronto. References to pivotal musical institutions (Canadian League of Composers, CBC, Canadian Music Centre, among others) and historical documents such as Ernest MacMillan’s Music in Canada, Marshall McLuhan’s Gutenberg Galaxy, and George Grant’s Lament for a Nation provide contextual frameworks for these perspectives.